Dendrostoma covidicola sp. nov. (Erythrogloeaceae, Diaporthales) on Fagus sylvatica from Sichuan Province, China - Samarakoon, Milan C.; Promputtha, Itthayakorn; Liu, Jian-Kui (Jack) (Phytotaxa, 2021)
Dendrostoma covidicola sp. nov. is described from a dead branch of Fagus sylvatica (Fagaceae) collected from Sichuan Province, China. The taxon has 5–20 perithecia per pseudostroma and small, ellipsoidal to subfusiform ascospores with polar appendages. Phylogenetic analyses of a combined ITS–LSU–rpb2–tef1 sequence matrix confirmed its placement in Dendrostoma where it is close to D. qinlingense, D. osmanthi and D. quercus, but representing a distinct lineage. The new taxon is compared with other Dendrostoma species and comprehensive descriptions and illustrations are provided. An ascospore comparison for relevant species is also provided, as well as an updated phylogenetic tree (ITS–LSU–rpb2–tef1) including all the species of Dendrostoma.